Nanoplasmonic probes of RNA folding and assembly during pre-mRNA splicing. Issue 8 (5th February 2016) - Nguyen, Anh H.; Lee, Jong Uk; Sim, Sang Jun
Abstract : RNA splicing plays important roles in transcriptome and proteome diversity. Abstract : RNA splicing plays important roles in transcriptome and proteome diversity. Herein, we describe the use of a nanoplasmonic system that unveils RNA folding and assembly during pre-mRNA splicing wherein the quantification of mRNA splice variants is not taken into account. With a couple of SERS-probes and plasmonic probes binding at the boundary sites of exon-2/intron-2 and intron-2/exon-3 of the pre-mature RNA of the β-globin gene, the splicing process brings the probes into the plasmonic bands. For plasmonic probes, a plasmon shift increase of ∼29 nm, corresponding to intron removal and exon-2 and exon-3 connection to form the mRNA molecule, is measured by plasmonic coupling. The increased scattering intensity and surface-enhanced Raman scattering (SERS) fingerprinting reveal the clear dynamics of pre-mRNA splicing. Moreover, a time-resolved experiment of individual RNA molecules exhibited a successful splicing and an inhibited splicing event by 33 μM biflavonoid isoginkgetin, a general inhibitor of RNA splicing. The results suggest that the RNA splicing is successfully monitored with the nanoplasmonic system. Thus, this platform can be useful for studying RNA nanotechnology, biomolecular folding, alternative splicing, and maturation of microRNA.